Genetic, Epigenetic and Transcription Factors in Atrial Fibrillation - O. V. Sapelnikov; A. A. Kulikov; O. O. Favorova; N. A. Matveeva; D. I. Cherkashin; O. A. Nikolaeva; R. S. Akchurin (Столичная издательская компания, 2019)
Atrial fibrillation (AF) is one of the most common arrhythmia that occurs in patients with cardiovascular diseases. Congenital forms of AF are quite rare. Many studies have shown that genetic, epigenetic and transcription factors may play an important role in the development and the progression of AF. In our review, studies have been conducted on the identification of mutations in ionic and non-ionic channels, possibly associated with AF. These mutations were found only in isolated groups of patients with AF, and in general, monogenic forms of AF are a rare subtype of the disease. Genomic association studies have helped to identify potential links between single nucleotide polymorphisms and AF. The risk of AF in the general population is likely to be determined by the interaction between environmental factors and many alleles. In recent years, the emergence of a genome-wide associative studies has significantly expanded the understanding of the genetic basis for the inheritance of AF and has led to the emergence of new evidence of the important role of genetic factors in the development of AF, in the risk stratification of AF and the recurrence of AF. Epigenetic factors are also important in AF. Epigenetic therapy aimed at treating a disease through exposure to epigenome is currently under development. A newly emerged area of ablatogenomics includes the use of genetic profiles that allow assessing the likelihood of recurrence of AF after catheter ablation. The results of genetic studies in AF show that, in addition to their role in the appearance of congenital heart pathologies, transcription factors play an important role in the pathogenesis of AF.